Primary frequency control applied to the wind turbine based on the DFIG controlled by the ADRC - Issam Minka; Ahmed Essadki; Sara Mensou; Tamou Nasser (Institute of Advanced Engineering and Science, 2019)
In this paper, we study the primary frequency control that allows the variable speed Aeolian to participate in the frequency regulation when a failure affects the network frequency. This method based on the control of the generator rotational speed or the control of pitch angle makes it possible to force the wind turbine to produce less power than its maximum available power, consequently we will create an active power reserve. This wind turbine must inject into the grid a part of its power reserve when the frequency drops, in contrary the wind turbine reserves more of energy. So, this work presents the performances of this control strategy for the different wind speed value. The results are obtained by a simulation in the MATLAB/SIMULINK environment.